Fucosylation Promotes Cytolytic Function and Accumulation of NK Cells in B Cell Lymphoma - Tong, Xing; Ru, Yuhua; Fu, Jianhong; Wang, Ying; Zhu, Jinjin; Ding, Yiyang; Lv, Fulian; Yang, Menglu; Wei, Xiya; Liu, Chenchen; Liu, Xin; Lei, Lei; et al. (Frontiers in Immunology, 2022)
Natural killer (NK) cells have been demonstrated as a promising cellular therapy as they exert potent anti-tumor immune responses. However, applications of NK cells to tumor immunotherapy, especially to the treatment of advanced hematopoietic and solid malignancies, are still limited due to the compromised survival and short persistence of the transferred NK cells in vivo. Here, we observed that fucosyltransferase (FUT) 7 and 8 was highly expressed on NK cells and the expression of CLA was positive correlated with the accumulation of NK cells in clinical B cell lymphoma development. Via enzyme-mediated ex vivo cell-surface fucosylation, the cytolytic effect of NK cells against B cell lymphoma was significantly augmented. Fucosylation also promoted NK cells accumulation in B cell lymphoma-targeted tissues by enhancing their binding to E-selectin. Moreover, fucosylation of NK cells also facilitated stronger T cell anti-tumor immune responses. These findings suggest that ex vivo fucosylation contributes to enhance effector functions of NK cells and may serve as a novel strategy for tumor immunotherapy.